2021
DOI: 10.31436/imjm.v20i2.1707
|View full text |Cite
|
Sign up to set email alerts
|

Metal Release of Standard and Fake Orthodontic Braces: An In Vitro Study

Abstract: INTRODUCTION: The growing demand for orthodontic braces among Malaysians has led to the development of fake braces. These fake braces services are illegal and their brackets are reported to be of inferior quality. Fake braces are constantly being exposed to the saliva intraorally, hence they are susceptible to corrosion. This study was conducted to investigate the release of metal ions as a result of corrosion from standard and fake orthodontic braces immersed in artificial saliva of different pH. MATERIALS AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In this study, it was noted that releases of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, and Cd ions were all below 10 mg/L over the 28-day immersion period, with no significant difference to the respective control samples, except for Mo. Nasir et al [ 8 ] also found less than 10 mg/L of Ni, Cr and Mn were released but the differences were significant compared to the control at day 1 for Cr and Mn, and at day 14 for Ni. It can be suggested that a systemic toxic effect from these ions is unlikely for fake braces, but if these results were to be compared with the daily dose recommended by WHO [ 18 ], some of the elements were higher than their limit.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this study, it was noted that releases of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, and Cd ions were all below 10 mg/L over the 28-day immersion period, with no significant difference to the respective control samples, except for Mo. Nasir et al [ 8 ] also found less than 10 mg/L of Ni, Cr and Mn were released but the differences were significant compared to the control at day 1 for Cr and Mn, and at day 14 for Ni. It can be suggested that a systemic toxic effect from these ions is unlikely for fake braces, but if these results were to be compared with the daily dose recommended by WHO [ 18 ], some of the elements were higher than their limit.…”
Section: Discussionmentioning
confidence: 72%
“…It was concluded that the bracket surfaces were distinctly inferior to those of the standard brackets and no heavy metals such as Pb, mercury (Hg) and arsenic (As) were present [ 6 ]. Another paper by the same author reported high releases of Cr, Mn and Ni ions from fake orthodontic brackets immersed in artificial saliva [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A local study identified increased metal ion release from orthodontic brackets bought from online suppliers. 24 The brackets are also presented with rough surfaces, making them prone to corrosion and breakage. 25 Two deaths in Thailand have been linked to the use of 'fake braces', which are commonly sold online.…”
Section: Discussionmentioning
confidence: 99%
“… Device Material Brand Released ions Study media Exposure time Analysis method Ref. Brackets Wires Fe–Cr–Ni–Mo Co–Cr–Mo–Fe Ti–Al–V Ni–Ti Cu–Ni–Ti Ormodent Cr Ni Fe Artificial saliva Elmex® mouthwash Meridol® mouthwash 2 months ICP-MS SEM Polarization curves [ 3 ] Ortho Plus Ormodent Ormodent Ormodent Brackets Wires SS NiTi SS 3 M Unitek - Tooth paste 12 h Friction test SEM [ 6 ] Brackets SS 3 M Unitek - Artificial saliva pH 4.9 pH 7.8 1 day ICP MS [ 7 ] Forestadent 7 days MEM Dental Technology 28 days Brackets SS Libral Traders - Artificial saliva 24 h Optical microscopy [ 8 ] Sodium chloride Pepper Turmeric Brackets Wires SS SS Ni Ti DynaLock - Artificial saliva Hydrofluoric acid Acid phosphate fluoride 24 h Friction force [ 9 ] Tomy Ormco 3M Unitek Ormco Brackets Wires Coated N...…”
Section: Bracketsmentioning
confidence: 99%